2022
DOI: 10.1002/batt.202200257
|View full text |Cite
|
Sign up to set email alerts
|

Designing Low‐Concentration Propylene Carbonate‐based Electrolyte by Manipulating Lithium+‐Solvation Structure for Graphite Anode

Abstract: We systematically study the correlation between Li+‐solvation structure, interfacial stability, and electrochemical behavior in the system of graphite anode with low‐concentration (0.5 M) propylene carbonate (PC)‐based electrolyte (LCPE). 1,1,2,2‐tetrafluoroethyl‐2,2,3,3‐tetrafluoropropylether (TTE) [or 1,1,2,2‐tetrafluoroethyl‐2,2,2‐trifluoroethyl ether (HFE)] is used to manipulate the solvation structures of Li+ in the LCPEs. Varying Li+‐solvation structures are realized by changing the volume ratios of PC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…[20] The finding is further supported by the Raman spectroscopic study. The EC/PC/EP electrolyte shows two distinct Raman peaks in the solvent band that unambiguously correspond to the solvated PC (852 cm −1 ) and solvated EP (864 cm −1 ) [21] (Figure 1e). The moderate Na + ‐solvation resulted from the low‐polarity EP solvent can lead to reduced Na + ‐desolvation energy and facilitate reaction kinetics at low temperatures [18] .…”
Section: Resultsmentioning
confidence: 99%
“…[20] The finding is further supported by the Raman spectroscopic study. The EC/PC/EP electrolyte shows two distinct Raman peaks in the solvent band that unambiguously correspond to the solvated PC (852 cm −1 ) and solvated EP (864 cm −1 ) [21] (Figure 1e). The moderate Na + ‐solvation resulted from the low‐polarity EP solvent can lead to reduced Na + ‐desolvation energy and facilitate reaction kinetics at low temperatures [18] .…”
Section: Resultsmentioning
confidence: 99%
“…42 With the addition of TTE, the signals of LiF and Li x PO y F z strengthen, suggesting that the addition of TTE promotes the involvement of anions in the CEI formation process. 43 It has been demonstrated that a LiFrich CEI can effectively restrain parasitic reactions between the cathode and the electrolyte, thereby improving the cycle stability and rate performance of LIBs. 38,44,45 In addition, the signal of lattice oxygen in the O 1s spectrum increases as TTE content grows.…”
Section: Resultsmentioning
confidence: 99%
“…The inert cosolvent 1,1,2,2‐tetrafluoroethyl‐2,2,3,3‐tetrafluoropropyl ether (TTE) was utilized to manipulate the solution structure as we mentioned in previous works. [ 10,11 ] The solution structures in the 1M‐ET11 and 1M‐ET12 electrolyte should be similar with the 2M‐E and 3M‐E electrolyte, respectively. The onset potential for PF6${\rm{PF}}_6^ - $ intercalation within the graphite cathode, the cycle and rate performances of Li||graphite and graphite||graphite cells, and the evolution of graphite intercalation compounds (GICs) in each electrolyte were systematically investigated.…”
Section: Introductionmentioning
confidence: 99%